Medieval pottery from the kiln site at Colstoun, E Lothian - Brooks, Catherine M; Betts, Ian M (Proceedings of the Society of Antiquaries of Scotland, 1981)
NT 520709. Excavation of two kilns yielded a very large assemblage of wheel-thrown vessels in typically pale fabric with thick yellow, green or brown glazes. Cooking pots and jugs predominate, the jugs decorated mostly with applied strips but also with face-masks; mid to later 13th century. A R